Infants younger than 6 months old infected by SARS-CoV-2 show the highest respiratory viral loads - Ochoa, Valeria Pilar (2021)
There is a paucity of reports on the characteristics of SARS-CoV-2 infection in infants, since most studies have grouped infants with older children. We analyzed the viral loads of 45,318 SARS-CoV-2-positive nasopharyngeal swab samples obtained in Buenos Aires, Argentina. Infants younger than 6 months old presented higher viral loads than any other age group. Children older than 6 months showed significantly lower viral loads, similar to those founds in adults. This observation raises new questions regarding the role of infants in the spreading of SARS-CoV-2 infection.